English language practical course for the 1st year students, semester 1 (все направления подготовки) электронный курс - Кудряшова, А. В. лингвист старший преподаватель Томского политехнического университета 1979- (TPU Moodle, 2023)
The course aims to develop listening, reading, writing and speaking skills, revise grammar material and increase vocabulary on the topics concerned. The course is developed for learning English for General Purposes by the first year students of TPU, 1st semester. The course covers such topics as education around the world, educational issues, learning strategies, modern skills and qualifications, jobs, job satisfaction, skills and qualifications, career opportunities, choosing a career path, success, recruitment and selection process, strategies of successful interview passing and job-hunting techniques as well as strategies for writing impressive CVs and covering letters.